Behavior and design of reinforced concrete building columns subjected to low-velocity car impact. (August 2020) - Sohel, K.M.A.; Al-Jabri, K.; Al Abri, A.H.S.
Abstract: Exposure of the columns on the first floor to lateral vehicular impact poses a great threat to the structural stability of buildings. In most cases, these columns may not be designed to resist the lateral impact force caused by the car-column collision. The dynamic impact force will cause deformation, reduce the bearing capacity of the column, and can cause catastrophic failure. In this study, the effect of a car impact on an axially loaded building column is evaluated by numerical simulation. An experimentally verified car model with a mass of 2203 kg and an axially loaded square reinforced concrete (RC) column model have been used for the numerical simulations. The results of the numerical analysis showed that the column-foundation joint is highly affected by the lateral impact force when the impact velocity is more than 30 km/h. A shear fracture occurs at the joint when the speed exceeds 40 km/h for columns with dimensions 400 mm or less. The axially loaded RC column has a higher impact resistance than columns without axial loads. From the impact force-time histories, the equivalent static forces (ESFs) have been calculated for the different ranges of impact velocities and different sizes of columns. It is found that the calculated ESF values are higher than the recommended values given by Eurocode 1. New proposed guidelines for the estimation of ESF and design recommendations are provided for the lateral impact load caused by a veered car on a building column.